2015
DOI: 10.1016/j.febslet.2015.04.040
|View full text |Cite
|
Sign up to set email alerts
|

VPS29–VPS35 intermediate of retromer is stable and may be involved in the retromer complex assembly process

Abstract: Edited by Lukas HuberKeywords: Retromer VPS35 VPS29 VPS26 Ubiquitin Proteasome Cation independent mannose-6-phosphate receptor SNXs a b s t r a c tRetromer is a complex of proteins that functions in the endosome-to-Golgi retrieval cargo transport pathway. VPS35 works as the central subunit of retromer to recognize the cargos and binds with VPS29 and VPS26 via distinct domains. We show that deficiency of VPS35 or VPS29 accompanies degradation of other subunits, whereas VPS26 deficiency had no effect on VPS29 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
5
20
0
Order By: Relevance
“…reported by(Fuse et al (2015) decrease in expression of VPS26 was also observed in VPS35177 KD cell which eventually tells us expression as well as functionality of VPS subunits are 178 interdependent (Fig. S2B).…”
mentioning
confidence: 58%
“…reported by(Fuse et al (2015) decrease in expression of VPS26 was also observed in VPS35177 KD cell which eventually tells us expression as well as functionality of VPS subunits are 178 interdependent (Fig. S2B).…”
mentioning
confidence: 58%
“…Consistent with this, loss of VPS35 destabilizes the retromer complex, resulting in reduced VPS26 and VPS29 protein, and this result has been confirmed both in vitro and in vivo (Cui et al, 2019;Liu et al, 2014;Wang et al, 2014). Similarly, knockdown or knockout of VPS29 in mammalian epithelial cell culture compromises retromer stability, causing loss of the other components (Fuse et al, 2015;Jimenez-Orgaz et al, 2017). Surprisingly, in the absence of Vps29 in Drosophila, we found that Vps35 and Vps26 are present at normal levels and remain tightly associated.…”
Section: Vps29 Is Required For Retromer Recruitment Via Rab7 and Tbc1d5mentioning
confidence: 74%
“…In prior studies of HeLa cell cultures, VPS29 knockdown caused reduced levels of both VPS35 and VPS26, likely due to destabilization of the retromer trimer complex and subunit turnover (Fuse et al, 2015;Jimenez-Orgaz et al, 2017). Reciprocally, enhancing interactions between VPS29 and VPS35 promotes retromer stability (Mecozzi et al, 2014;Young et al, 2018).…”
Section: Vps29 Regulates Retromer Localization and Is Required In Thementioning
confidence: 94%
See 1 more Smart Citation
“…The over-expression of the top 25 genes in hepatic schistosomula appears to reflect a diversity of physiological activities, including transcriptional (homeobox protein engrailed-like SMOX-2 [47, 48], serum and glucocorticoid-regulated kinase 1 (SGK1) [49] and nuclear receptor subfamily 4 group A [50, 51]) and neuronal (protocadherin FAT4 [52], Aromatic-L-amino-acid decarboxylase [53] and delphilin [54]) activities, together with tegumental integrity (annexin A3 [55, 56]), skeletal morphogenesis (protocadherin FAT4 [57]) and endosome-to-Golgi retrieval (vacuolar protein sorting-associated protein 29 [58]).…”
Section: Resultsmentioning
confidence: 99%